2006
DOI: 10.1093/intimm/dxl107
|View full text |Cite
|
Sign up to set email alerts
|

The anti-microbial peptide LL-37 inhibits the activation of dendritic cells by TLR ligands

Abstract: The endogenous anti-microbial peptide LL-37/hCAP-18 is an effector molecule of the innate host defense system at surfaces of the body. Besides its direct anti-microbial activity, the peptide interacts with different cell types. Dendritic cells (DCs) play a central role in mucosal host defense. It was the aim of the study to determine whether LL-37 modulates the response of DCs to pathogen-associated molecular patterns. Monocyte-derived DCs were stimulated with the Toll-like receptors (TLRs) ligands LPS, lipote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
121
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 34 publications
7
121
2
Order By: Relevance
“…Indeed, antimicrobial molecules such as LL-37, lactoferrin, and a-defensins can inhibit DC activation (33,54,56,57). In addition, elastase can induce TGF-b (32) and reduce proinflammatory cytokine production by moDC, thus promoting CD4 + lymphocyte T regulatory polarization (31).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, antimicrobial molecules such as LL-37, lactoferrin, and a-defensins can inhibit DC activation (33,54,56,57). In addition, elastase can induce TGF-b (32) and reduce proinflammatory cytokine production by moDC, thus promoting CD4 + lymphocyte T regulatory polarization (31).…”
Section: Discussionmentioning
confidence: 99%
“…For example, LL-37 can activate macrophages to produce inflammatory cytokines in response to microbial stimuli and induce efficient phagocytosis of IgGopsonized bacteria (40). The peptide can modulate the differentiation of monocytes to DCs that promote the development of a Th subset expressing high levels of IFN-g and low/undetectable levels of IL-4/IL-5 (18), although maturation of the LL-37-differentiated DCs by several TLR ligands may be suppressed (19). In addition, it can enhance plasmacytoid DCs to produce IFN-a in response to self-DNA (41).When the infection recedes due to removal of pathogens and cellular debris by phagocytes, the levels of LL-37/GM-CSF in the local environment subside to homeostatic levels that facilitate differentiation of monocytes to macrophages with the "default" anti-inflammatory signature again.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its antimicrobial actions, LL-37 participates at the interface of innate and adaptive immunity by modulating cytokine and chemokine production by a range of cell types, chemoattracting various immune effector cells (14) and mesenchymal stem cells (15), regulating autophagy in conjunction with vitamin D (16), and stimulating angiogenesis and wound healing (17). Others reported that LL-37 enhances the GM-CSF/IL-4-driven differentiation of blood monocytes to immature DCs (18), whereas inhibiting the maturation of immature DCs by TLR ligands (19). Furthermore, this peptide enhances the responses of monocytes (and macrophages) to GM-CSF and IL-1b (20,21), but suppresses those to IFN-g (22), indicating that LL-37 affects the responses of mononuclear phagocytes to cytokines differentially.…”
mentioning
confidence: 99%
“…However, soluble mediators including IL-10, TSLP, TGF-b, NO and prostaglandins have also been implicated in the generation of an organ-specific microenvironment [18]. Also, the anti-microbial peptide LL-37 has been reported to alter DC phenotypes in the lung [33]. In our experiments we observe that soluble mediators can transfer the inhibitory potential of epithelial cells; however, cell contactdependent mechanisms might also been operative as suggested for intestinal epithelial cells and DC [31].…”
Section: Discussionmentioning
confidence: 99%